Red cell distribution width is associated with stroke severity and unfavorable functional outcomes in ischemic stroke - Xue, Jie; Zhang, Dong; Zhang, Xiao-Guang; Zhu, Xiao-Qiong; Xu, Xu-Shen; Yue, Yun-hua (Frontiers in Neurology, 2022)
Background Red blood cell distribution width (RDW) is considered to be related to coronary heart disease and heart failure and all-cause mortality, but its relationship with acute ischemic stroke is still unclear. In this study, we aimed to explore the relationship between RDW and the stroke severity and functional outcomes of ischemic stroke. Methods We retrospectively reviewed patients with acute ischemic stroke between September 2016 and January 2020. Demographic, clinical, stroke complications, laboratory data, and treatment were collected for all patients. Stroke severity and functional outcomes were evaluated by NIHSS score, modified Rankin Scale (mRS), and Barthel Index (BI) at 3 months. Furthermore, multiple logistic regression analysis was used to assess the relationship between RDW and stroke severity and functional outcomes. Results A total of 629 patients with acute ischemic stroke were included and were categorized into four groups according to the quartiles of RDW (< 12.4, 12.4–12.9, 13.0–13.4, > 13.4). After multivariable analysis, higher RDW was directly associated with moderate to severe stroke (OR 2.21, 95% CI, 1.30–3.75, P = 0.003), mRS score of 3–6 at 3 months (OR 1.86, 95% CI, 1.02–3.41, P = 0.044), and BI score below 85 at 3 months (OR 2.27, 95% CI, 1.25–4.12, P = 0.007) in patients with ischemic stroke. Conclusion Our results demonstrate that RDW is associated with stroke severity and unfavorable functional outcomes at 3 months in patients with ischemic stroke.